2019
DOI: 10.7554/elife.46007
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-mediated control of developmental lymphangiogenesis

Abstract: The post-transcriptional mechanisms contributing to molecular regulation of developmental lymphangiogenesis and lymphatic network assembly are not well understood. MicroRNAs are important post-transcriptional regulators during development. Here, we use high throughput small RNA sequencing to identify miR-204, a highly conserved microRNA dramatically enriched in lymphatic vs. blood endothelial cells in human and zebrafish. Suppressing miR-204 leads to loss of lymphatic vessels while endothelial overproduction o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…Rescue experiments demonstrated that a balanced expression of these two factors is essential to ensure proper lymphatic vessel network formation during lymphatic development. In this study, it was found that only a small fraction of the identified LEC-enriched miRNAs were conserved among vertebrate species, leading to the hypothesis that LEC miRNAs may display a divergent evolution for mammalian-specific functions (Jung et al, 2019). Given the important role of FOXO1 discussed in the previous section, it is of interest that a recent study has reported that miR-182 negatively regulates the expression of FOXO1 in zebrafish (Kiesow et al, 2015) where miR-182 is crucial for the regular formation of the paracordal lymphangioblasts and the thoracic duct (Kiesow et al, 2015).…”
Section: Mirnas As Powerful Post-transcriptional Actors That Control ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Rescue experiments demonstrated that a balanced expression of these two factors is essential to ensure proper lymphatic vessel network formation during lymphatic development. In this study, it was found that only a small fraction of the identified LEC-enriched miRNAs were conserved among vertebrate species, leading to the hypothesis that LEC miRNAs may display a divergent evolution for mammalian-specific functions (Jung et al, 2019). Given the important role of FOXO1 discussed in the previous section, it is of interest that a recent study has reported that miR-182 negatively regulates the expression of FOXO1 in zebrafish (Kiesow et al, 2015) where miR-182 is crucial for the regular formation of the paracordal lymphangioblasts and the thoracic duct (Kiesow et al, 2015).…”
Section: Mirnas As Powerful Post-transcriptional Actors That Control ...mentioning
confidence: 99%
“…In addition to the presented studies with a role in the regulation of PROX1 and VEGFR3, a recent study from Jung and co-authors comprehensively investigated the role of miRNAs in lymphatic development (Jung et al, 2019) and identified miR-204 as the first lymphatic-specific miRNA. In zebrafish, loss of miR-204 leads to a reduction in lymphatic vessel formation, suggesting miR-204 as a positive regulator of lymphatic development, likely by binding to and modulating the expression of the NFATC1 transcription factor (Figure 4B).…”
Section: Mirnas As Powerful Post-transcriptional Actors That Control ...mentioning
confidence: 99%
“…For the data analysis, we focused primarily on the endpoint of embryonic development and sex determination and differentiation. In the functional characterization, novel miRNA-145-col9a3 was reported to be involved in gonad development, as Col9a3 encodes the α3 chain of type IX collagen, which is expressed during mouse testis development (Venø et al, 2017;Jung et al, 2019). Another mouse study demonstrated the specified expression of Col9a3 in testicular cords during the early stages of gonadal differentiation (Hanson-Kahn et al, 2018).…”
Section: Novel Mirna_290 Dync1li2mentioning
confidence: 99%
“…They can be adapted to virtually any experimental need, by choosing the most suitable promoter (for total body or tissue-specific expression); gene of interest (non-coding, but also coding. Of note, besides sponge-204 or pre-miR-204, the vectors here described also express the coding eGFP mRNA, for a total transcript length of ∼1 kb); mechanism and degree of gene modulation [overexpression ( Jung et al, 2019 ); downregulation using RNA interference ( Giacomotto et al, 2015 ); knock in ( Prykhozhij and Berman, 2018 ) or knock out ( Kaufman et al, 2016 ; Ablain et al, 2018 ; Jung et al, 2019 ) using CRISPR/Cas9 technology].…”
Section: Resultsmentioning
confidence: 99%